"Cardio‐Oncology": Implications for interventionists. Issue 5 (April 2016) - Goldstein, James A.
Key Points: CV complications in cancer patients predominantly result from collateral damage from chemotherapy and radiation Complex interplay of manifold pathophysiologic processes poses evaluation challenges and management conundrums. Pre‐cath planning essential, employing advanced non‐invasive imaging of myocardium, PC, and great vessels.